2013
DOI: 10.1159/000346370
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Brain Levels of Urate and Precursors in Parkinson's Disease and Related Disorders

Abstract: Background: Increasing evidence suggests that urate may play an important role in neurodegenerative disease. In Parkinson's disease (PD) higher, but still normal, levels of blood and cerebrospinal fluid urate have been associated with a lower rate of disease progression. Objective: We explored the hypothesis that lower levels of urate and its purine precursors in brain may be associated with PD and related neurodegenerative disorders, including Alzheimer's disease (AD) and Lewy body dementia (DLB). Methods: Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 40 publications
3
43
1
Order By: Relevance
“…Church and Ward in 1994 (150) examined postmortem caudate and substantia nigra samples from PD patients and controls (n=4 for each group) and found that urate levels were lower in the SN (p<0.05) and caudate (p<0.1) of PD patients compared with controls, consistent with others and our subsequent findings in a larger post-mortem series (151, 152). They also observed a higher dopamine oxidation rate constant in PD compared to the control striatum homogenates, supporting a “pro-oxidative stress” state in PD.…”
Section: Urate Levels In Pd Brainsupporting
confidence: 77%
“…Church and Ward in 1994 (150) examined postmortem caudate and substantia nigra samples from PD patients and controls (n=4 for each group) and found that urate levels were lower in the SN (p<0.05) and caudate (p<0.1) of PD patients compared with controls, consistent with others and our subsequent findings in a larger post-mortem series (151, 152). They also observed a higher dopamine oxidation rate constant in PD compared to the control striatum homogenates, supporting a “pro-oxidative stress” state in PD.…”
Section: Urate Levels In Pd Brainsupporting
confidence: 77%
“…Thereby, an abnormal content of urea and related amino acids has been previously found in serum [19,20,33] and brain [8,9] of AD, accompanied by altered levels of expression in different enzymes and the corresponding genes [40]. Other studies reported an increased concentration of inosine in response to an accelerated degradation of nucleotides in brain from human patients [41] and APP/PS1 mice [9], which is finally reflected in peripheral blood as revealed our metabolomic fingerprinting platform. However, Jiang et al surprisingly described the lack of inosine in serum from the SAMP8 mice [12], demonstrating the disparity between different existing models of AD and the need to select the correct one to mimic metabolic features detected in human AD.…”
Section: Biological Hypothesissupporting
confidence: 53%
“…36 In a recent postmortem study, urate levels in cortical and striatal tissue was lower in PD compared to controls in men only. 37 The biological mechanisms underlying such sex specificity remain unclear. Interestingly, several cardiovascular risk factors, such as hypercholesterolemia 38 and hypertension, 39 have been reported to be associated with increased risk of PD in women but not in men.…”
Section: Resultsmentioning
confidence: 99%